2012
DOI: 10.1021/jm3006542
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 3-(5-Chloro-2-furoyl)-3,7-diazabicyclo[3.3.0]octane (TC-6683, AZD1446), a Novel Highly Selective α4β2 Nicotinic Acetylcholine Receptor Agonist for the Treatment of Cognitive Disorders

Abstract: Diversification of essential nicotinic cholinergic pharmacophoric elements, i.e., cationic center and hydrogen bond acceptor, resulted in the discovery of novel potent α4β2 nAChR selective agonists comprising a series of N-acyldiazabicycles. Core characteristics of the series are an exocyclic carbonyl moiety as a hydrogen bond acceptor and endocyclic secondary amino group. These features are positioned at optimal distance and with optimal relative spatial orientation to provide near optimal interactions with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Recent work by Targacept with the development of AZD1446 (3-(5-chloro-2-furoyl)-3,7-diazabicyclo [3.3.0]octane), a highly selective a4b2 nAChR agonist, has shown that bioisoteric replacement of pyridine as the hydrogen bond acceptor (HBA) is a viable strategy for drug discovery in nAChR [20]. The alkaloid epibatidine (1) has long been known as a potent ligand for a4b2 and other nAChRs with adverse effects on CNS responses, respiration, GI and cardiovascular function.…”
Section: Molecular Design Binding Affinity and Functional Datamentioning
confidence: 99%
“…Recent work by Targacept with the development of AZD1446 (3-(5-chloro-2-furoyl)-3,7-diazabicyclo [3.3.0]octane), a highly selective a4b2 nAChR agonist, has shown that bioisoteric replacement of pyridine as the hydrogen bond acceptor (HBA) is a viable strategy for drug discovery in nAChR [20]. The alkaloid epibatidine (1) has long been known as a potent ligand for a4b2 and other nAChRs with adverse effects on CNS responses, respiration, GI and cardiovascular function.…”
Section: Molecular Design Binding Affinity and Functional Datamentioning
confidence: 99%
“…However, it failed to demonstrate improvement in cognition in a large study of stable patients with schizophrenia treated with an atypical antipsychotic [47]. A third a 4 b 2 NNR agonist, AZD1446, improved attention and memory in rodents [48]. Although it was well tolerated in humans, it failed to show improvement in cognitive functioning in subjects with ADHD [49].…”
Section: Expert Opinionmentioning
confidence: 99%
“…This was followed up by a more robust randomized, double-blind, placebo-controlled, crossover study of ABT-418 with 236 patients, where the compound demonstrated significant improvement on the primary outcome compared with placebo, as well as in several secondary outcome measures [67]. AZD1446 (7, TC-6683) is a highly selective agonist of central α4β2 and α2β2 neuronal nicotinic receptors [68]. The compound, which is in phase II, has been shown to improve cognition in multiple animal models and has demonstrated potential for treatment of cognitive disorders, including Alzheimer's disease (AD) and schizophrenia.…”
Section: α4β2 Nachr Agonists and Partial Agonists For Schizophreniamentioning
confidence: 99%